2019
DOI: 10.3389/fcimb.2019.00202
|View full text |Cite
|
Sign up to set email alerts
|

How Ocular Surface Microbiota Debuts in Type 2 Diabetes Mellitus

Abstract: High glucose represents a good environment for bacterial growth on the skin, on the ocular surface (OS) and in the tears of type 2 diabetes mellitus (T2DM) patients, affecting the conjunctival bacterial community. This study aimed to investigate the OS bacterial flora of T2DM patients and healthy subjects using 16S rRNA sequencing-based bacterial identification. Among 23 healthy subjects (CON) and 31 T2DM patients, 54 eyes were examined to investigate the OS bacterial community. Factors potentially affecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
39
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 26 publications
8
39
1
Order By: Relevance
“…In T2DM, the altered gut microbiota potentially affect the fecal metabolome, the immune status and the intestinal redox status and inflammation (Lopez- de-Andres et al, 2018;Piccolo et al, 2018;Wang et al, 2018;Tian et al, 2019). T2DM was reportedly affected by the decrease of butyrate-producing species in rats (Li et al, 2019;Zhou et al, 2019). In our study, we observed that levels of Bifidobacterium and Faecalibaculum had significantly increased after DJB-sa.…”
Section: Figure 4 | (A)mentioning
confidence: 47%
“…In T2DM, the altered gut microbiota potentially affect the fecal metabolome, the immune status and the intestinal redox status and inflammation (Lopez- de-Andres et al, 2018;Piccolo et al, 2018;Wang et al, 2018;Tian et al, 2019). T2DM was reportedly affected by the decrease of butyrate-producing species in rats (Li et al, 2019;Zhou et al, 2019). In our study, we observed that levels of Bifidobacterium and Faecalibaculum had significantly increased after DJB-sa.…”
Section: Figure 4 | (A)mentioning
confidence: 47%
“…The high prevalence of bacterial growth can be explained by the alteration of immunity due to diabetes (Grzybowsky et al, 2017;Adam et al, 2015;Karimsab and Razak, 2013;El-Mollayess et al, 2012;Martins et al, 2004). Others authors have reported that hyperglycemia and high-grade systemic inflammation in diabetic patients may promote the growth and colonization of potential pathogens (Li et al, 2019;Fernandez-Rubio et al, 2010). In the literature, the proportion and ratio of positive cultures of diabetic participants and controls varies among authors.…”
Section: Discussionmentioning
confidence: 99%
“…67 High glucose levels in the tears and increased ocular surface inflammation with diabetes support increased microbial growth. 68 Using traditional culture techniques, greater frequency of Escherichia coli, Klebsiella pneumoniae and enterococci have been identified on the ocular surface of patients with diabetes compared with healthy controls. [69][70][71] Higher positive culture rates and greater bacterial diversity were associated with increasing severity and duration of diabetes disease, respectively.…”
Section: Corneamentioning
confidence: 99%